2016
DOI: 10.1080/03075079.2016.1203890
|View full text |Cite
|
Sign up to set email alerts
|

Quality of working life of academics and researchers in the UK: the roles of contract type, tenure and university ranking

Abstract: Quality of Working Life has been defined as the part of overall quality of life that is influenced by work. We developed a mediation model where homework interface, job and career satisfaction, control at work, and working conditions are considered to be positively related to employee commitment and to the absence of stress at work. These two variables were ultimately related to general well-being. We considered possible differences between workers with different contract types (permanent vs. temporary), as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…The temporality of contracts (e.g. permanent vs. temporary staff) may also influence the relationships observed in this research as previous work in the sector has already shown (Fontinha, Van Laar and Easton, 2016). Then again, the current grouping of employment roles meets the purpose of our research, which was to focus on the moderating effect that two specific task characteristics (low and high structured) and two different role positions (with and without leadership responsibilities) can have on the relationship between governance practices and well-being.…”
Section: Limitationsmentioning
confidence: 79%
“…The temporality of contracts (e.g. permanent vs. temporary staff) may also influence the relationships observed in this research as previous work in the sector has already shown (Fontinha, Van Laar and Easton, 2016). Then again, the current grouping of employment roles meets the purpose of our research, which was to focus on the moderating effect that two specific task characteristics (low and high structured) and two different role positions (with and without leadership responsibilities) can have on the relationship between governance practices and well-being.…”
Section: Limitationsmentioning
confidence: 79%
“…Work-Life Balance. This construct was measured using the three HWI items of the WRQoL1 scale (Easton & Van Laar, 2012;Fontinha et al, 2016) and refers to the perceived context provided by the organization to have a balance between work and personal life. This factor has a sub-scale reliability of  =.85 in these data and picks up on the importance of balancing home and work demands (Dorsey, Jarjoura & Rutecki, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…This scale 6 contains six factors: individual's perceptions of whether their organization provides them with a balanced home-work interface (HWI)this will be an independent variable in our model named work-life balance; perceptions about the physical working conditions available (WCS); job and career satisfaction (JCS); perceptions regarding the level of control over decision making at work (CAW); levels of stress, or its absence, at work (SAW); and general well-being (GWB). A seventh factor, which assesses level of employee commitment to the organization (ECO) has been used in ongoing research and development of the WRQoL scale, and is also used here (Fontinha et al, 2016). We focus on these dimensions, the dependent variables in our model, in order to characterize the quality of working life of academics and non-academics working in nine HEIs in the United Kingdom.…”
Section: Academics Vs Non-academics' Quality Of Working Lifementioning
confidence: 99%
See 1 more Smart Citation
“…By contributing to a broader and more holistic understanding of research 'productivity' that encompasses the quality of intellectual engagement, our findings could be used to support positive iQoL among stakeholders in academia, including faculty, staff, postdoctoral fellows, students and administrators. Previous research has addressed related concepts, such as quality of work life (QWL) [28], quality of working life [29], or quality of academic worklife (QAWL) [18], that mainly address the various tasks associated with one's professional role. However, our conceptualization of iQoL contributes a unique focus on the intellectual, or 'thinking' aspects of academic life that extend beyond a traditional work boundary.…”
Section: Discussionmentioning
confidence: 99%